Effects of Policy and Resources on Antimicrobial Stewardship Interventions in the VA: Applying a Transaction Cost Economics Framework. (4th October 2017) - Chou, Ann; Zhang, Yue; Jones, Makoto; Graber, Christopher J; Goetz, Matthew; Madaras-Kelly, Karl; Samore, Matthew; Kelly, Allison; Glassman, Peter
Abstract: Background: Inappropriate antimicrobial use poses a serious threat to patient safety. Various antimicrobial stewardship interventions (ASI) have been proposed to optimize antimicrobial use and improve patient outcomes, but ASI implementation remains an organizational challenge. This study examines associations between policy and resources and ASI implementation/uptake in VA facilities. Methods: Implementing new practices requires changes in organizational structure, culture, and work. As ASIs require coordination among staff and activities, the transaction cost economics (TCE) perspective is used to examine ASI uptake. TCE dimensions describe: (1) uncertainty; (2) frequency of interactions; and (3) asset specificity. Using a cross-sectional design, surveying 140 VA facilities in 2015, outcomes examined were: (1) facility tracking 3 or more ASIs; and (2) barriers to optimal antimicrobial use. Independent variables include those describing site specificity, resources, and various AS policies as proxies for uncertainty. Multivariable logistic regressions with Least Absolute Shrinkage and Selection Operator approach was used to identify the subset of variables and generate odds ratios across TCE dimensions associated with ASI uptake. Results: Infectious disease attendings in medical wards, clinical pharmacists assigned to teams, documentation of indication in medical record/order entry, policies on intravenous to oral conversion, electronic tools were associated with greater ASI uptake. Similar variables also decreased the likelihood of facilities experiencing barriers to optimal antibiotic use. Conclusion: Overall, site specificity, human resources, physical assets, and policies facilitated ASI uptake and ameliorated barriers to optimal antimicrobial use. These variables represent mechanisms that improved efficiencies of coordination and provided resources to achieve stewardship goals. ASI uptake represents a complex change, requiring a system-wide response. The TCE framework is useful to inform facilities in their strategies to adopt new ways of organizing in order to manage emerging demands of changing clinician work, coordinate across units/departments, and develop tools to optimize antimicrobial use. Disclosures: All authors: No reported disclosures.